Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV SONNE during cruise SO256 - Mahyar Mohtadi; Robin J Beaman; JR Pall; KL Sanborn; Lena Mary O extquotesingleToole (PANGAEA, 2024)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg EM 710 multibeam echosounder was not continuously recorded during RV SONNE cruise SO256. Data was recorded on 10 days between 2017-04-21 and 2017-05-08. This dataset contains mostly transit data in the Great Barrier Reef (coastal waters) including some survey lines close to the Australian coast, Torres Strait, Arafura Sea and Tmor Sea. The approximate average depth of the entire dataset is around 200m. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. Ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus SVP files are added to this dataset. Also data analysis of the multibeam raw data revealed that SVP has been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality is rather good since the gridded hillshade data showed relatively few obstacles. Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2023).